Exploring the impact of acute solvent exposure on larval zebrafish behaviour - Hagen, Ethan V.; Harper, Matthew M. M.; Zhang, Yanbo; Hamilton, Trevor J. (Frontiers in Behavioral Neuroscience, 2025)
Zebrafish (Danio rerio) are commonly used to test the impact of pharmacological and toxicological compounds. Larval zebrafish are extensively used because of high throughput procedures allowing simultaneous behavioural measurement in 24-, 48-, or 96-well plates. Often solvents are used as a vehicle for poorly soluble or insoluble compounds, however, the impact of dimethyl sulfoxide (DMSO), methanol, and ethanol after acute administration is not well characterized. Here we investigated the impact of 30-min exposures of DMSO, methanol, and ethanol (0.01%, 0.1%, and 1.0% vol/vol) on 5-day old larval zebrafish locomotion and startle responses. We found no effect of DMSO on distance moved and thigmotaxis in a spontaneous swimming test, and no effect on dark-, light-, or tap-startle responses compared to controls. Methanol and ethanol, both at 1.0% increased the distance moved, and ethanol decreased the dark startle response at 1.0%. Neither ethanol nor methanol had any impact on time in thigmotaxis zone, light- or tap-startle responses. Results from this study suggest that with acute exposure to experimental compounds requiring a solvent, the least impact on behaviour would occur with DMSO, followed by methanol, then ethanol.